Muscle Contraction Induces Acute Hydroxymethylation of the Exercise-Responsive Gene Nr4a3 - Pattamaprapanont, Pattarawan; Garde, Christian; Fabre, Odile; Barrès, Romain (Frontiers in Endocrinology, 2016)
Exercise training triggers numerous positive adaptations through the regulation of genes controlling muscle structure and function. Epigenetic modifications, including DNA methylation, participate in transcriptional activation by allowing the recruitment of the transcription machinery to gene promoters. Exercise induces dynamic DNA demethylation at gene promoters, however the contribution of the demethylation precursor hydroxymethylcytosine is unknown. Given the evanescent nature of hydroxymethylcytosine, a muscle contraction model that allows for the collection of samples that are repeatedly stimulated over time is required to determine whether contraction-induced demethylation is preceded by changes in the hydroxymethylcytosine level. Here, we established an acute skeletal muscle contraction model to mimic the effects of acute exercise on gene expression. We used this model to investigate the effect of muscle contraction on DNA demethylation and hydroxymethylation. First, we performed an acute exercise study in healthy humans to identify an exercise-responsive gene that we could study in culture. We identified nuclear receptor subfamily 4 group A member 3 (Nr4a3) gene showed the highest fold-expression increase after acute exercise. We then refined an Electrical Pulse Stimulation (EPS) protocol in C2C12 myotubes capable to change the expression of the Nr4a3 gene. Using targeted bisulfite sequencing, we found that in response to EPS, a region of the Nr4a3 promoter is rapidly demethylated at 60 minutes and re-methylated at 120 minutes. Of interest, hydroxymethylation of the differentially methylated region of Nr4a3 promoter after EPS was elevated immediately after EPS, with lowest levels reached at 60 minutes after EPS. In conclusion, we have established a cell culture-based protocol to mimic the acute transcriptional responses to exercise. Furthermore, we provide insight into the mechanism by which the exercise-responsive gene Nr4a3 is demethylated after muscle contraction.